Pigeon Point, Tobago - Yhap, Christine (Printed by CPPP Ltd.,[Trinidad and Tobago], 2011)
The postcard offers a scenic view of Pigeon Point one of the more popular tourist spots on the island of Tobago. Postcard number F8.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Beaches--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Seashore--Trinidad and Tobago; Coasts--Trinidad and Tobago; Huts--Trinidad and Tobago; Jetties--Trinidad and Tobago; Piers--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago; Beachgoers--Trinidad and Tobago; Trees--Trinidad and Tobago; Thatched roofs--Trinidad and Tobago; [1995]